2012
DOI: 10.1111/j.1553-2712.2012.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

The 2011 Model of the Clinical Practice of Emergency Medicine

Abstract: The 2011 Model of the Clinical Practice of Emergency Medicine. ACADEMIC EMERGENCY MEDICINE 2012; 19:000–000 © 2012 by the Society for Academic Emergency Medicine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Focused bedside renal US for the detection of hydronephrosis by emergency physicians (EP) is an established practice and is now integrated within the core emergency medicine curriculum of residency training programs 4. The finding of hydronephrosis on emergency bedside US is an indirect sign of a ureteral stone and has a reported sensitivity of 72–83% when compared to CT 5,6…”
Section: Introductionmentioning
confidence: 99%
“…Focused bedside renal US for the detection of hydronephrosis by emergency physicians (EP) is an established practice and is now integrated within the core emergency medicine curriculum of residency training programs 4. The finding of hydronephrosis on emergency bedside US is an indirect sign of a ureteral stone and has a reported sensitivity of 72–83% when compared to CT 5,6…”
Section: Introductionmentioning
confidence: 99%
“…The Model of the Clinical Practice of Emergency Medicine23 (EM Model) serves as the basis for the content specifications for all American Board of Emergency Medicine (ABEM) examinations 24. The knowledge required to practice competent EM increases daily.…”
Section: Discussionmentioning
confidence: 99%
“…The GEMC are high impact geriatric topics developed by Hogan et al and identified through expert consensus as most important in the emergency care of older adults 22,23. The GEMCs were used as a basis for development of an educational intervention, and multiple choice assessment tool.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, extensive changes were made to Appendix 1 and Appendix 2. Appendix 1 became category “19.0 Procedures and Skills Integral to the Practice of Emergency Medicine” under the table of “Medical Knowledge, Patient Care, and Procedural Skills”; Appendix 2 became category “20.0 Other Core Competencies of the Practice of Emergency Medicine.” Within each of these two sections, additional changes were made . All of these changes were approved by the collaborating organizations and the revised Model was published electronically in Academic Emergency Medicine in July 2012.…”
Section: Evolutionmentioning
confidence: 99%